Gastric Cancer Surgery During the Pandemic: What It Costs? - YEGEN, ŞEVKET CUMHUR; UPRAK, TEVFİK KIVILCIM (SPRINGER, 2021)
Background From the early days of 2020, the COVID-19 pandemic continues to change whole life all around the world. Oncological patients are the most affected populations since these days. Because of decreasing numbers in surgery and endoscopy, gastric cancer patients had difficulties in treatment and diagnoses. Therefore, the early and long-term results may be affected during the pandemic. In this study, we aimed to evaluate pandemia effects on gastric cancer surgery in a single center. Patients-Methods Patients were categorized as the COVID group and the Pre-COVID group. Patients who received neoadjuvant chemotherapy were excluded from the study. In the COVID period, 50 patients underwent gastric cancer surgery, while 64 were operated on in the pre-COVID period. Patients' demographics and clinical and pathological outcomes were evaluated. Results There was no statistically significant difference in both periods among patient characteristics such as age, gender, and body mass index. Pre-operative laboratory results were similar between two groups. Although there was no difference in operation types, an increase was detected in Clavien-Dindo grade 3 and higher complications during the COVID period. During the pandemic, there was a significant difference in the pathological outcomes. Peritoneal cytology-positive patients were higher in the COVID group. More lymphovascular invasions were also detected in the COVID period. Finally, it resulted stage differences between two groups. Conclusion Because of COVID-19's heavy burden on healthcare system, delays in the diagnosis and treatment of oncological patients may occur. Therefore, this may be affected pathological and survival outcomes of cancer patients. Finally, further investigations are needed.
Keywords: Cancer; COVID; Gastric; Pathology; TREATMENT DELAY; WAITING TIME; SURVIVAL; IMPACT